Teyl by Using Songs and Games in Students’ Learning Motivation - Siti Ratna Sari (Yayasan Insan Mulia Bima, 2025)
This study aimed at finding out whether the use of songs and games in teaching English to young learners give an effect in students' learning motivation at MI Brawijaya Trowulan, Mojokerto. In order to achieve the goal of the study, quasi experimental design was utilized. In this study was used 2 classes as the sample, they are experimental group and control group. The questionnaires were used to collect the data. Then the data were analyzed by using Analysis of Covariance (ANCOVA) through SPSS 24. In the process of English teaching learning, the researcher applied 2 songs which are “Jobs Song” and “Eat and Drink All Day Long” and 2 games which are “Suit Game” and “The Mime Game”. The study revealed that TEYL by using songs and games could make young learners enjoy and feel fun the learning process, enthusiastic, become confident to perform, and involved to be participant. Consequently, the result of this study has enhanced the students’ learning motivation.